Health Education With A Balanced Nutrition Pocketbook For Pregnant Women In The First Trimester - Dian Kumalasari, Elis; Nurrasyidah, Rahmi; Kuswati, Kuswati (Yayasan Inspirasi El Burhani, 2024)
Introduction: Chronic energy deficiency can affect the growth of the fetus. Based on a preliminary study, 80% of pregnant women do not understand nutrition in early pregnancy. health education aims to make pregnant women healthier than before. The pocketbook has more flexible characteristics, is easy to carry anywhere, and can be read anytime. Objective: This study aims to determine the effect of health education with pocketbooks on knowledge of balanced nutrition in pregnant women in the first trimester. Method: This is a quantitative research type, pre-experiment one group pre-post test design without control. The population in this study were all pregnant women in the first trimester at the Independent Practice of Midwife Noris Hadi in February – March including 25 pregnant women. The sampling technique used was total sampling. The intervention was health education with the lecture method and discussion with pocketbook media. Data were analyzed univariately and bivariately. The instrument used a questionnaire that had been tested for validity and reliability. Result: Almost all respondents are aged 20-35 years, pregnant women with a college education are very low, and most are working women. there were no pregnant women in the first trimester who experienced a decrease in scores after being given health education. The average increase in the score of 24 pregnant women was 12.5 points. There was 1 pregnant woman in the first trimester who had the same pre-test and post-test results. Conclusion: there is a difference in test results before and after being given Health Education with a pocketbook regarding knowledge of balanced nutrition for pregnant women.